Using Traditional Flashcard to Teach the Present Progressive Tense - Octaviani, Berliana Pingky; Soepriatmadji, Liliek (research, training and philanthropy institution Natural Aceh, 2024)
In recent years, learning technology has developed very rapidly. However, many schools have not been fully facilitated, so they still use conventional learning media. The purpose of this research is to find out whether traditional flashcards as a learning tool can improve the present progressive tense and how grade 3 students at SD N 01 Trimulyo see the use of traditional flashcards as a learning tool. In this study, data were collected through observation and interviews. Grade 3 students of SD N 01 Trimulyo became the object of this research. Researchers also conduct tests to find out how research findings develop. This study uses a qualitative methodology and a qualitative descriptive approach. The results of the study show that traditional flashcards can be used as alternative learning media in today's digital and internet era. This medium really helps teachers. Students feel happier and find it easier to learn English after using traditional flashcards. Students are more motivated to learn because learning using traditional flashcards is easier for them to understand. In the world of education, the traditional use of flashcards is still a new method. Traditional flashcards are a solution for schools that do not yet have sufficient facilities in today's modern and digital era.